An Analysis of Bioinformatics Applications and Overview (International Journal of Food and Nutritional Sciences, 2022)
Data overload has made many biological problems computational problems. Bioinformatics,which uses computer methods to analyse biomolecule data on a massive scale, has become amajor field in molecular biology, including structural biology, genomics, and gene expressionresearch.Recent technological advances have advanced phenotypic genetics research.Genomic breakthroughs have transformed biological problems on a genome-wide scale,exposing an avalanche of data and bringing up numerous options. However, Moore's law andbiological information processing must overcome the massive volume of information created.Bioinformatics and computational biology have addressed these issues. This reviewintroduces and summarises the field. We explain bioinformatics concepts, the sorts ofbiological information and databases utilised, and some of the investigations being done,notably on transcription regulatory systems.